THE QUESTION OF THE OPPIDA VETERIS LATII IN PLINY THE ELDER'S NATVRALIS HISTORIA. (6th May 2018) - Espinosa-Espinosa, David
Abstract : This article attempts to provide a plausible explanation of a series of expressions used by Pliny the Elder to designate a significant number of communities in Hispania: [oppida] Latio antiquitus donata, [oppida] Latinorum ueterum, oppidani Latii ueteris, [oppida] Latii antiqui and oppida ueteris Latii (Plin. HN 3.7, 3.18, 3.24, 3.25, 4.117). These phrases, commonly explained from a chronological or typological viewpoint, encompass fifty Augustan ciuitates, the most important feature of which was the enjoyment of Latin rights before the sources used by Pliny were written under the Early Principate. To address this issue, the meaning and the use of the term oppidum are first examined. In a second stage, the origin and the sense of the adjectives uetus and antiquum, as well as the adverb antiquitus, are analysed. The results suggest that oppida ueteris Latii and its variants may express, in a simple and comprehensible way, the administrative changes that a group of Republican Latin colonies in Hispania underwent through their transformation into municipia Latina during the reign of Augustus.